(untitled) (International Journal of Food and Nutritional Sciences, 2022)
In the modern world, solid waste management has strategic ramifications. The need to balance environmental protection with economic growth is driving attention towards the non-linear economy’s potential. The management of solid and liquid wastes should focus on methods that treat, recycle, and reduce wastes by treating them like resources. This Research article‘s objective is to examine circular economy and ecological protection for sustainable environmental livelihood and its theoretical and practical waste management is concerns from the standpoint of cross-disciplinary eco-economic collaboration, using the concepts of the circular economy